THE IMPACT OF COGNITIVE BEHAVIORAL THERAPY ON OCD’S PATIENTS - Aleksandra Dorosz; Weronika Wawrzynów; Agnieszka Skoczeń; Magdalena Maria Jakubowska; Adrian Kruk; Dominika Walczak; Błażej Kaczmarek (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Cognitive Behavioral Therapy (CBT) is a well-established, empirically supported intervention for Obsessive-Compulsive Disorder (OCD). OCD is a chronic, debilitating condition marked by intrusive thoughts (obsessions) and repetitive behaviors or mental acts (compulsions) aimed at reducing distress or preventing feared outcomes. Affecting 1-3% of the global population, OCD significantly impairs functioning, relationships, and quality of life. CBT, particularly Exposure and Response Prevention (ERP), is a cornerstone of OCD treatment. It helps individuals confront obsessions and resist compulsions, disrupting the cycle that maintains symptoms. Through systematic exposure to feared stimuli and prevention of habitual responses, CBT promotes anxiety habituation and cognitive restructuring.Material and Methods: Literature was gathered via PubMed, the Clinical Handbook of Psychological Disorders edited by David H. Barlow, and references from retrieved articles.Results: OCD is a chronic illness that markedly lowers quality of life and often co-occurs with other disorders such as depression or anxiety. CBT, especially ERP, is more effective than pharmacotherapy. Neuroimaging studies (e.g., fMRI) confirm positive changes in brain activity after CBT. Regular homework between sessions is crucial for maintaining therapeutic gains.Conclusion: Research confirms that CBT, particularly ERP, addresses core OCD mechanisms. It modifies dysfunctional thinking and behavior, reducing symptoms and improving functioning. Exposure exercises and response prevention build coping skills and reduce compulsions and obsessions. Consistent completion of therapeutic tasks, including homework, is essential for lasting outcomes. These findings highlight CBT’s efficacy as a primary treatment for OCD.